2000
DOI: 10.1074/jbc.c000326200
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Phosphoprotein Cbp Positively Regulates the Activity of the Carboxyl-terminal Src Kinase, Csk

Abstract: Csk (carboxyl-terminal Src kinase) is a cytoplasmic tyrosine kinase that phosphorylates a critical tyrosine residue in each of the Src family kinases (SFKs) to inhibit their activities. Recently, we identified a transmembrane protein, Cbp (Csk-binding protein), that, when phosphorylated, can recruit Csk to the membrane where the SFKs are located. The Cbp-mediated relocation of Csk to the membrane may play a role in turning off the signaling events initiated by SFKs. To further characterize the Csk-Cbp interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 19 publications
3
151
0
Order By: Relevance
“…As shown in Fig. 3B, Cbp IPs from normal thymocytes were capable of phosphorylating poly EY efficiently, and this phosphorylation was almost completely blocked by the addition of Cbp-4 phosphopeptide which contains Tyr 314 and is known to compete with Cbp-Csk interaction (12). Another phosphopeptide, Cbp-2, which cannot interfere with the binding of Cbp to Csk was not able to inhibit the phosphorylation of poly EY.…”
Section: The Amount and The Kinase Activity Of Csk Associated With Cbmentioning
confidence: 91%
See 3 more Smart Citations
“…As shown in Fig. 3B, Cbp IPs from normal thymocytes were capable of phosphorylating poly EY efficiently, and this phosphorylation was almost completely blocked by the addition of Cbp-4 phosphopeptide which contains Tyr 314 and is known to compete with Cbp-Csk interaction (12). Another phosphopeptide, Cbp-2, which cannot interfere with the binding of Cbp to Csk was not able to inhibit the phosphorylation of poly EY.…”
Section: The Amount and The Kinase Activity Of Csk Associated With Cbmentioning
confidence: 91%
“…Once recruited to rafts and activated by Cbp, Csk would inhibit the kinase activity of Lck through phosphorylation of an Lck C-terminal tyrosine to keep resting T cells in a quiescent state. The Csk-Cbp complex has been shown to have a greater affinity for Src than free Csk (12). Although Fyn itself could be a target of Csk in rafts, it has been demonstrated that the kinase activity of Fyn is relatively difficult to be suppressed by Csk compared with those of other Src family PTKs (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cbp/ PAG binds to and recruits CSK to the plasma membrane by virtue of a tyrosine phosphorylation site on Cbp/PAG and the SH2 domain in CSK. Binding of Cbp/PAG to CSK also appears to activate CSK (Takeuchi et al, 2000). The tyrosine kinase responsible for the phosphorylation of Cbp/PAG is currently unknown.…”
Section: Ptp1b and Other Ptps That Might Target C-srcmentioning
confidence: 99%